PENDIDIKAN PEMILIH DALAM MENINGKATKAN PARTISIPASI POLITIK MASYARAKAT PADA PEMILIHAN UMUM SERENTAK 2019 - Anang Dony Irawan (Universitas Muhammadiyah Tangerang, 2019)
Decision of the Constitutional Court Number 14 / PUU-XI / 2013 in the test case of Law Number 42 of 2008 concerning General Elections of the President and Vice President whose decisions are final states that the holding of the 2019 General Elections and subsequent General Elections shall be held simultaneously. The holding of a simultaneous General Election in 2019 will certainly bring political impacts, both nationally and regionally. The birth of Law No. 7 of 2017 concerning General Elections has had a major impact and challenge for the Indonesian people in improving the electoral system and the implementation of better democracy. The purpose of this study is to find out how to realize political education for voters ahead of the 2019 simultaneous elections. This study is a juridical normative approach to legislation. From the results of the study there is a legal vacuum that requires the General Election Commission to conduct Socialization, Voter Education, and Community Participation in the 2019 Elections. The resulting conclusion is that political education for voters ahead of the 2019 concurrent elections is very important to carry out, as an effort to realize the Sovereignty of a Strong State. The resulting recommendation is to make a legal rule regarding the obligation to carry out political education for voters ahead of the 2019 simultaneous elections in an effort to realize the Strong Sovereign State Voters in the 2019 Election along with the threat of sanctions for election administrators in an Act intensifying political education for voters ahead of the Election in an effort to realize voters sovereignty in the next general election along with the existence of technical rules regarding sanctions for election administrators in a law. Communities need to be encouraged to be actively involved in updating their population data to the relevant offices that handle population administration.Keywords : 2019 Election, Voter Education, Strong Sovereign State Voters, Constitutional Court, General Election Commission.